A Hyperactive RelA/p65-Hexokinase 2 Signaling Axis Drives Primary Central Nervous System Lymphoma - Tateishi, Kensuke; Miyake, Yohei; Kawazu, Masahito; Sasaki, Nobuyoshi; Nakamura, Taishi; Sasame, Jo; Yoshii, Yukie; Ueno, Toshihide; Miyake, Akio; Watanabe, Jun; Matsushita, Yuko; Shiba, Norio; et al. (Cancer research (Chicago, Ill.), 2020)
Primary central nervous system lymphoma (PCNSL) is an isolated type of lymphoma of the central nervous system and has a dismal prognosis despite intensive chemotherapy. Recent genomic analyses have identified highly recurrent mutations of MYD88 and CD79B in immunocompetent PCNSL, whereas LMP1 activation is commonly observed in Epstein-Barr virus (EBV)-positive PCNSL. However, a lack of clinically representative preclinical models has hampered our understanding of the pathogenic mechanisms by which genetic aberrations drive PCNSL disease phenotypes. Here, we establish a panel of 12 orthotopic, patient-derived xenograft (PDX) models from both immunocompetent and EBV-positive PCNSL and secondary CNSL biopsy specimens. PDXs faithfully retained their phenotypic, metabolic, and genetic features, with 100% concordance of MYD88 and CD79B mutations present in PCNSL in immunocompetent patients. These models revealed a convergent functional dependency upon a deregulated RelA/p65-hexokinase 2 signaling axis, codriven by either mutated MYD88/CD79B or LMP1 with Pin1 overactivation in immunocompetent PCNSL and EBV-positive PCNSL, respectively. Notably, distinct molecular alterations used by immunocompetent and EBV-positive PCNSL converged to deregulate RelA/p65 expression and to drive glycolysis, which is critical for intracerebral tumor progression and FDG-PET imaging characteristics. Genetic and pharmacologic inhibition of this key signaling axis potently suppressed PCNSL growth and . These patient-derived models offer a platform for predicting clinical chemotherapeutics efficacy and provide critical insights into PCNSL pathogenic mechanisms, accelerating therapeutic discovery for this aggressive disease. SIGNIFICANCE: A set of clinically relevant CNSL xenografts identifies a hyperactive RelA/p65-hexokinase 2 signaling axis as a driver of progression and potential therapeutic target for treatment and provides a foundational preclinical platform. GRAPHICAL ABSTRACT: http://cancerres.aacrjournals.org/content/canres/80/23/5330/F1.large.jpg.